Double Disillusion The 2016 Australian Federal Election - Gauja, Anika; Chen, Peter; Curtin, Jennifer; Pietsch, Juliet (ANU Press, 2018)
"This book provides a comprehensive analysis of the 2016 Australian federal election. Won by the Liberal-National Coalition by the slimmest of margins, the result created a climate of political uncertainty that threatened the government's lower house majority. While the campaign might have lacked the theatre of previous elections, it provides significant insights into the contemporary political and policy challenges facing Australian democracy and society today. In this, the 16th edited collection of Australian election studies, 41 contributors from a range of disciplines bring an unprecedented depth of expertise to the 2016 contest. The book covers the context, key battles and issues in the campaign, and reports and analyses the results in detail. It provides an evaluation of the role of political actors such as the parties, independents, the media, interest groups and GetUp!, and examines election debate in the online space. Experts from a range of policy fields provide an analysis of election issues ranging from the economy and industrial relations to social policy, the environment, and gender and sexuality. Each of the chapters is written on the basis of in‑depth and original research, providing new insights into this important political event."